The combined effect of energy density and hollow microspheres additive on structural and wear properties of polyamide 11 composites produced via selective laser sintering - Cingoz, Umut Can; Kisasoz, Burcin Ozbay; Kisasoz, Alptekin (ELSEVIER, 2025)
This study investigated the production and properties of polyamide 11 matrix hollow ceramic microsphere reinforced composites. The composites were produced at 10 wt% and 20 wt% reinforcement ratios by selective laser sintering using different energy density values. The influence of the energy density values and hollow ceramic microsphere additive on the properties of the samples was determined. The ceramic microspheres provided the production of lightweight samples. Moreover, the wear behaviour of the samples improved significantly with a combined effect of the energy density and usage of ceramic-based microsphere. The wear rate was reduced to 2.75 & sdot;10-4 mm3/Nm at 0.0500 J/mm2 energy density and 20 wt% reinforcement ratio.
Keywords: Additive manufacturing; Polymer; Composite; Wear; Materials Science; Physics